A radiographic criteria checklist to determine reasons for errors, resulting in sub-optimal routine shoulder projections - Ida-Keshia Sebelego; Belinda van der Merwe; Jeanette du Plessis (AOSIS, 2019)
Background: Optimal shoulder images must adhere to specific radiographic criteria before they are sent to the radiologist for reporting. Repeat x-rays of the shoulder may increase radiation exposure to the patient. Aim: The aims of this study were to determine whether images adhered to the required radiographic criteria for routine shoulder imaging and to identify possible reasons for non-adherence. Setting: The study was conducted at an imaging department at a tertiary academic hospital in Bloemfontein, South Africa. Methods: A criteria checklist compiled from literature was used to evaluate 578 routine shoulder images including anteroposterior (AP) with external rotation and lateral-Y (LAT-Y) projections. The checklist determined whether the shoulder images adhered to the criteria with regard to the anatomy included, positioning and technical factors, such as inclusion of the correct anatomical lead marker. Data were analysed using SAS Version 9.2 statistical software. Results: More than 80% of the AP external rotation images included unnecessary anatomical structures owing to incorrect centring. In four out of seven criteria pertaining to positioning for AP external rotation imaging, at least 70% of images were performed incorrectly. Four-sided collimation was not present in more than 50% of both AP external rotation and LAT-Y images because of incorrect centring, while more than 30% of shoulder images presented with anatomical digital markers. Conclusion: The application of criteria required for shoulder imaging must be addressed at the participating imaging department to improve overall patient care. An in-service training session is recommended to enhance the radiographic technique with regard to routine shoulder projections.